Structure of A High-Speed Rail Corridor: Long-term planning implications for sustainable regional development along High-Speed Rail Corridor - BHARULE, Shreyas (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Along the High-Speed Rail (HSR) corridors in Asia and Europe, trade migration has intensified economic networks between cities and created an urban-regional development ecosystem where cities along the HSR corridor form a mega-region and reinforce each other. However, throughout the literature, the introduction of HSR has mainly been associated with the urban service sector. Therefore, it has become necessary to identify the implications for regional land development strategies. This paper summarizes the key areas impacted by HSR infrastructure investments that aid in creating a region of impact. The work focuses on creating a theoretical framework for the structure of the HSR corridor. The framework is based on a literature review and a case study of established HSR projects worldwide.